Guru Muthmainnah dalam Perspektif Kyai Pesantren (Studi Terhadap Tiga Kyai Pimpinan Pondok Pesantren Wali Songo Ngabar Ponorogo Jawa Timur) - Muhammad Suyudi; Azam Syukur Rahmatullah (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2017)
This study aims to know about muthmainnah teachers according to the thought of kyai in Islamic Boarding School Wali Songo, Ngabar, Ponorogo East Java. This research used qualitative method with three sample of kyai Pondok Pesantren Wali Songo Ngabar Ponorogo. The results of this study showed that Guru muthmainnah is a noble position to be had when teachers apply the aspects of takhalli, tahalli, which will ultimately gain enlightenment of soul, thought and behavior, can be achieved by walking the spiritual-divine paths such as; al-musyarathah, almuraqabah, al-muhasabah, and al-mujahadah.